Migration decision making : multidisciplinary approaches to microlevel studies in developed and developing countries - De Jong, Gordon F.; Gardner, Robert W. (Pergamon policy studies on international development., 1981)
Migration Decision Making: Multidisciplinary Approaches to Microlevel Studies and Developing Countries discusses several topics, such as systematics review and evaluation of microlevel frameworks and models of the migration decision; applicability of microlevel migration models and framework; and general policy implications of microlevel models and frame works. The opening chapter introduces the main themes and provides an overview of the book. Chapter 2 discusses the motivation for migration, an assessment and a value-expectancy research model, and the next chapter tackles macrolevel influenc.